Contact pressure-dependent friction compensation in upsetting tests with miniaturized specimens - Hetz, Peter; Rentz, Marcel; Merklein, Marion (Materials Research Proceedings, 2023)
Components produced by sheet metal forming can so far only be characterized locally to a limited extent using conventional tests, such as the tensile test or the hydraulic cupping test, due to the size of the specimen. A new approach based on miniaturized upsetting specimens taken from the sheet plane allows to determine the material properties of semi-finished products locally, for example in radii. However, in addition to this specific advantage, challenges such as friction between the specimen and the tool also appear with this testing method. For an accurate determination of the material parameters, it is therefore necessary to correct the test force by the friction coefficient. According to the state of the art, a variety of tests for friction coefficient characterization exist. By using a novel numerical method, friction coefficients for upsetting tests can be calculated contact pressure-dependent by means of an experimental single layer upsetting test. Therefore, in this paper, this method will be used for the first time to compensate the friction part in an upsetting test with miniaturized specimens as a function the contact pressure. This can improve the experimental mapping of the material behavior in the uniaxial compression stress state with increasing strain and hardening, since share of friction force increases with a higher deformation in the upsetting test. In contrast, a friction coefficient compensation based on an average value is provided in order to analyze, whether or in which case a contact pressure-dependent friction compensation is appropriate. In particular, for upsetting tests with miniaturized specimens, these results are relevant, since a major advantage of this test compared to conventional tests besides the local component characterization is the determination of material properties at high strains.
CRIS-Team Scopus Importer:2023-04-28
Keywords: Friction; Metal Forming; Upsetting Test